PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA RESIDIVIS DALAM PELAKSANAAN PERADILAN - Irawansyah Irawansyah; Arwan Pradoki; Rudi Aryanto; Reza Febriansyah; Sheva Febrian; M. Yoslan; Hutomo; Samsul Samsul; Ravil Mulawarman; Adi Syahputra; Juli Juli; Yusni Dewi; Ridho Nasution; Erwin Syahputra (Nusantara Hasana Journal, 2022)
Recidive is one of thereasons ballast criminal, where the imposition of the sentence plus onethird of the maximum criminal threats. Recidive provision stipulated in Book II Of The Criminal Code of The Crime Of Article 386, 387 and 388 KUHP. Someone can be said to be a offenden recidive or recidivist when they fulfill the requirements for recidive. Judges in imposing criminal against recidive should really considen the purpose of the criminal law one of which is for the pupose of justice not only in consideration but really should convict fairest. With existence of law expected by state Indonesia become peaceful state and can prevent the happening of crime. Its function criminal law arrange life of society to be can create orderliness of public. These time often met by various crime case conducted by recidivist, where the recidivist don’t discourage to penalization which he have against the punismentin prison previously. Research problems of this study are (1) How arrangement of law to recidivist according to positive law in Indonesia? ( 2) How base consideration of judge in breaking a recidivist? This research use approach of normatif that is with method approach of legislation, conceptual, and approach of case.